Perceptions of business graduates in Egypt on incorporating data analytics into the business curriculum - Ahmed Diab; Samar El Sayad (Cogent Education)
The advent of data analytics has disrupted the business professions. It has not only created new job positions but also transformed established jobs. The business curriculum is expected to undergo a technological change to prepare students to be competitive in the job market. However, minimal studies have explored the incorporation of new technologies such as data analytics in business education, especially in the context of developing countries. This study aims to investigate the importance of incorporating data analytics into the business curriculum in Egypt. In doing so, a questionnaire was distributed to business school graduates in Egypt to explore their perceptions regarding the importance of incorporating data analytics in the business curriculum, the data analytics tools that should be incorporated into the business curriculum, and whether individual and work-related factors can affect their perceptions. The final sample consisted of 191 respondents. Descriptive statistics, t-test and ANOVA were used to analyze the data. Generally, incorporating data analytics in the business curriculum was perceived as necessary. Also, the findings showed that work experience and profession influenced the respondent’s perceptions regarding integrating data analytics into the business curriculum. The findings of this study can direct the attention of education authorities and universities to the importance of integrating data analytics into business curricula.